Enunciation and Translation in ‘Quarto de despejo: diário de uma favelada’ and ‘Child of the Dark: The Diary of Carolina Maria de Jesus - Soares, Poliana; Kunz, Marinês Andrea (Revista Letras Raras, 2021)
This paper is an interdisciplinary analysis involving the discursive literary genre diary, Linguistics and Translation. It discusses self-writing through the assumptions of Lejeune (2008), associated with Benveniste’s (2005, 2006) Theory of Enunciation, relating to categories of person, time, and space to the idea that every translation is a rewriting and manipulation (LEFEVERE, 2007). The objective is to demonstrate that the translation of Carolina de Jesus' work called Quarto de Despejo: diário de uma favelada (QD) into English is the result of a new enunciation that does not necessarily kept the expression of the subjectivity of the original one, changing its meaning. Next, a comparative analysis of the QD’s excerpts and from its respective American translation — Child of the Dark: the diary of Carolina Maria de Jesus —, is carried out based on the marks and traits contained in both enunciations and the effects of meaning created by them. The exploratory and bibliographic comparison between the works ratifies the enunciation as the establishment of the subject into it and the translation as a generational process of a new enunciation that seeks to prevail the original meanings, but it does not fully accomplish it.